2022
DOI: 10.1021/acs.jpcc.2c02717
|View full text |Cite
|
Sign up to set email alerts
|

Can We Replace Cr(VI) as a Homogeneous Catalyst in the Chlorate Process?

Abstract: The chemistry of hypochlorous acid in the presence of metal impurities is of high importance for many areas of chemistry ranging from water purification and disinfection to sea water splitting and the electrosynthesis of chlorate. The production of chlorate comprises one of the most important electrochemical processes and relies on the Cr­(VI) catalyzed transformation of HOCl to chlorate. Since the use of Cr­(VI) has been restricted in the European Union due to its toxicity, mutagenicity, and carcinogenicity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 72 publications
2
10
0
Order By: Relevance
“…In Figure 6a the molar flow of oxygen is shown, the change at low telluric acid addition is not significant however the addition of 33.5 mM telluric acid results in a lower oxygen formation which is in line with previous theoretical and experimental studies [39,46] . It is also clearly shown that the reference system with sodium dichromate reduces the oxygen formation significantly.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…In Figure 6a the molar flow of oxygen is shown, the change at low telluric acid addition is not significant however the addition of 33.5 mM telluric acid results in a lower oxygen formation which is in line with previous theoretical and experimental studies [39,46] . It is also clearly shown that the reference system with sodium dichromate reduces the oxygen formation significantly.…”
Section: Resultssupporting
confidence: 88%
“…Amongst these compounds deprotonated telluric acid ([Te(OH) 5 (O)] À ) has been identified as a possible catalyst candidate. [39] These predictions were also confirmed by the experimental work of Szabo et al, [46] who showed, that indeed a real catalytic process takes place. [16,46] The comparison of the results obtained using Cr(VI) versus deprotonated telluric acid reveals that the former is a more active catalyst.…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations